Erythropoietic Agents and the Elderly - Agarwal, Neeraj (2008)
Erythropoietin is a peptide hormone that stimulates erythropoiesis. There are several agents in clinical use and in development, which either act as ligands for the cell surface receptors of erythropoietin or promote erythropoietin production that stimulates erythropoiesis. These are known as erythropoietic agents. The agents already in use include epoetin alfa, epoetin beta, and darbepoetin alfa. Newer agents stimulating erythropoiesis (such as continuous erythropoietin receptor activator (CERA) or proline hydroxylase inhibitors that increase HIF-1 thereby stimulating erythropoietin production and iron availability and supply) are under active investigation. Erythropoietic agents have been shown to promote neuronal regeneration and to decrease post-stroke infarct size in mouse models. They have also been reported to shorten survival when used to treat anemia in many cancer patients and to increase thromboembolism. In contrast, rapid decrease of erythropoietin levels as observed in astronauts and high-altitude dwellers upon rapid descent to sea level leads to the decrease of erythroid mass, a phenomenon known as neocytolysis. The relative decrease in the serum erythropoietin level is known to occur in some subjects with otherwise unexplained anemia of aging. Anemia by itself is a predictor of poor physical function in the elderly and is a significant economic burden on society. One out of every five persons in the United States will be elderly by 2050. Erythropoietic agents, by preventing and treating otherwise unexplained anemias of the elderly and anemia associated with other disease conditions of the elderly, have the potential to improve the functional capacity and to decrease the morbidity and mortality in the elderly, thereby alleviating the overall burden of medical care in society.